Experiences of enhanced recovery after surgery in general gynaecology patients: An interpretative phenomenological analysis. Issue 2 (July 2019) - Phillips, Eleanor; Archer, Stephanie; Montague, Jane; Bali, Anish
There is little qualitative research exploring non-cancer gynaecology patients' experiences of enhanced recovery after surgery (ERAS) protocols. Seven women participated in audio-recorded interviews, discussing their experiences of enhanced recovery after surgery for gynaecological surgery. Data were transcribed and analysed using interpretative phenomenological analysis. Three themes were identified: meeting informational needs, taking control of pain, and mobilising when feeling fragile. Control emerged as a key element throughout the themes and was supported by provision of factual information. While participants were generally satisfied with their experience, topics such as concerns about analgesic use, the informal role of staff in mobilisation, and the expressed desire for more experiential information for participants require further research.